Superlubricity of Graphene/C60/Graphene Interface - Experiment and Simulation - Naruo Sasaki (Japanese Society of Tribologists, 2012)
We investigated the nano-scale superlubricity or ultralow friction appeared at the graphene/C60/graphene interface, where the (mean) lateral force becomes nearly zero within the atomic resolution of the frictional force microscopy (FFM). The C60 intercalated graphite film is one of the most successful systems we have developed as the graphene/C60/graphene interface, and it exhibits an excellent friction coefficient, μ<0.001. Simulated superlubricity of the graphene/C60/graphene interface shows the marked anisotropy with a period of the scan direction of 60°, which reflects the symmetry of the six-membered rings of the C60 molecule and graphene sheet. The physical origins of the maximum peak and near-zero minimum are numerically clarified. Controlling supelubricity of the graphene/C60/graphene interface will contribute to solving the energy and environmental problems.